Zoopoetikens tankar om språk och art: En bakgrundsteckning - Björck, Amelie (Tidskrift för litteraturvetenskap, 2022)
Thoughts on Language and Species in Zoopoetics – a Background Sketch Amelie Björck Zoopoetic studies investigate “texts that are, in one way or another, predicated upon an engagement with animals and animality (human and nonhuman),” to quote Kári Driscoll and Eva Hoffman. A central question in this field concerns the relation between language and species. This article suggests that two basic views can be discerned: one that conceptualizes language as a human-specific capacity, and another that frames language as a broader phenomenon that humans and most other species have in common. These two starting points – the first accentuating differences, the second emphasizing similarities – give rise to two different approaches to zoopoetry. In the first case, zoopoetry is associated with the deconstruction of human semantics and, thus, of human power. In the second case, zoopoetry is seen as an experiment in which the attentive human poet comes together with animals in a natural act of mutual poiesis. The aim of the article is to uncover the genealogy of these two views – here named the “language sceptic” perspective and the “language affirmative” perspective, respectively – and to problematize them as scholarly reading positions. Using examples from Les Murray’s animal poetry, the article argues that the two perspectives might more fruitfully be explored as two dimensions that exist and create interesting friction within zoopoetic texts – hence an oscillation between the perspectives is preferable.